Relationships between fatigue, cognitive function, and upright activity in a randomized trial of oxaloacetate for myalgic encephalomyelitis/chronic fatigue syndrome - Vernon, Suzanne D.; Rond, Candace; Sun, Yifei; Roundy, Shad; Bell, Jennifer; Rond, Bella; Kaufman, David L.; Cash, Alan B.; Yellman, Brayden; Bateman, Lucinda (Frontiers in Neurology, 2025)
BackgroundMyalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a debilitating condition characterized by fatigue, cognitive impairment, and reduced physical function. Oxaloacetate (OAA), a metabolic compound with potential mitochondrial and neuroprotective effects, has shown promise in reducing fatigue symptoms in ME/CFS. However, the interrelationships between fatigue, cognitive performance, and physical activity and their responsiveness to treatment remain poorly understood in ME/CFS.MethodsThis 90-day randomized, double-blind, controlled trial evaluated the effects of 2,000 mg/day OAA or a control of 2,000 mg rice flour in 82 adults with ME/CFS. Self-reported fatigue (Chalder Fatigue Questionnaire), cognitive function (DANA Brain Vital), and upright activity time (UP Time) were assessed at baseline and three follow-up visits. Linear mixed-effects models examined associations between fatigue severity and cognitive/physical function, with treatment group interactions. Responder status at the last visit (Visit 4) was classified based on ≥15% fatigue reduction and/or ≥10% cognitive improvement.ResultsThe OAA group showed greater cognitive improvement over time, with a significant between-group difference at Visit 3, 60 days into the trial, (p = 0.034) and trends at other visits. Higher fatigue was significantly associated with reduced cognitive gains in the OAA group (β = −0.34, p < 0.0001), but not in controls. UP Time increased modestly in the OAA group, reaching significance at Visit 2, day 30 (p = 0.044), though fatigue was not a strong predictor of UP Time in either group. At Visit 4, day 90, Global and Fatigue Only Responders were more frequent in the OAA group, while Cognitive Only Responders were more frequent in controls, though group differences did not reach statistical significance (p = 0.10).ConclusionOAA supplementation was associated with improved cognitive performance and small improvement in UP Time in ME/CFS participants receiving OAA. Fatigue–cognition coupling was particularly strong in OAA-treated participants, suggesting a potentially targetable phenotype. These findings underscore the importance of multidimensional outcome measures in ME/CFS clinical trials and support the need for more research and trials of metabolic interventions in ME/CFS.